High Temperature Endurable Fiber Optic Accelerometer - Yeon-Gwan Lee; Jin-Hyuk Kim; Chun-Gon Kim (Shock and Vibration)
This paper presents a low frequency fiber optic accelerometer for application in high temperature environments of civil engineering structures. The reflection-based extrinsic fiber optic accelerometer developed in this study consists of a transmissive grating panel, reflective mirror, and two optical fiber collimators as the transceiver whose function can be maintained up to 130°C. The dynamic characteristics of the sensor probe were investigated and the correlation between the natural frequency of the sensor probe and temperature variation was described and discussed. Furthermore, high temperature simulation equipment was designed for the verification test setup of the developed accelerometer for high temperature. This study was limited to consideration of 130°C applied temperature to the proposed fiber optic accelerometer due to an operational temperature limitation of commercial optical fiber collimator. The sinusoidal low frequency accelerations measured from the developed fiber optic accelerometer at 130°C demonstrated good agreement with that of an MEMS accelerometer measured at room temperature. The developed fiber optic accelerometer can be used in frequency ranges below 5.1 Hz up to 130°C with a margin of error that is less than 10% and a high sensitivity of 0.18 (m/s2)/rad.